Effect of catchment land use and soil type on the concentration, quality, and bacterial degradation of riverine dissolved organic matter - Autio, Iida; Soinne, Helena; Helin, Janne; Asmala, Eero; Hoikkala, Laura (Springer, 2016)
We studied the effects of catchment characteristics (soil type and land use) on the concentration and quality of dissolved organic matter (DOM) in river water and on the bacterial degradation of terrestrial DOM. The share of organic soil was the strongest predictor of high concentrations of dissolved organic carbon, nitrogen, and phosphorus (DOC, DON, and DOP, respectively), and was linked to DOM quality. Soil type was more important than land use in determining the concentration and quality of riverine DOM. On average, 5-9 % of the DOC and 45 % of the DON were degraded by the bacterial communities within 2-3 months. Simultaneously, the proportion of humic-like compounds in the DOM pool increased. Bioavailable DON accounted for approximately one-third of the total bioavailable dissolved nitrogen, and thus, terrestrial DON can markedly contribute to the coastal plankton dynamics and support the heterotrophic food web.
Keywords: terrestrial dissolved organic matter; catchment characteristics; bacterial degradation; DOM quality; bioavailability; boreal catchments; growth efficiency; carbon; export; DOM; bioavailability; marine; absorbency; nutrients; Northern Baltic Sea